Vanilloid-mediated apoptosis in prostate cancer cells through aTRPV-1 dependent and a TRPV-1-independent mechanism - Ziglioli, F.; Frattini, A.; Maestroni, U.; Dinale, et al., F. (Acta Biomedica Atenei Parmensis, 2009)
Vanilloids are natural molecules identified in a plethora of foods normally ingested through the diet. They mediate apoptosis through a direct pathway (independent of TRPV-1, the receptor for vanilloids) and through an indirect pathway, i.e. thanks to the interaction with TRPV-1 and the successive intracellular calcium growth [Ca2+]i. Some vanilloids, such as capsaicin, dihydrocapsaicin and resiniferatoxin (the ultrapotent analogue of capsaicin, extractable from Euphorbia resinifera), may be considered as coenzyme Q antagonists: in fact, they inhibit the run of the electrons through the electron transport chain, so determining an excess of reactive oxygen species (ROS). A second effect of the interaction between the vanilloids and TRPV-1 receptor may be reported: it is the fast decrease of the transmembrane mitochondrial potential (ΔΨm). Through the direct pathway, on the contrary, the vanilloids induce apoptosis also interacting with caspases, particularly caspase 1 and 3. On the whole, the vanilloids are able to lead to the intracellular calcium growth and consequently to the evidence of precocious and late elements of apoptosis.